Therapeutic role of mesenchymal stem cells in neurogenesis for management of neurological disorders: a scientometric study to an in-depth review - Wang, Qian; Jiang, Weifeng; Feng, Yan; Li, Lin; Chu, Lisheng; Fang, Yan (Frontiers in Neurology, 2025)
BackgroundThe biological process of neurogenesis involves the production of new and completely functional neurons in two specific regions of the brain: the ventricular-subventricular zone (V-SVZ) and the subgranular zone (SGZ) of the hippocampal dentate gyrus by neural stem cells (NSCs). Interfering with this mechanism harms the brain and may result in neurological disorders. Cell-based therapies are becoming recognized as optimal possibilities for facilitating neurogenesis. To comprehend the many processes and mechanisms of neurogenesis and the role of mesenchymal stem cells (MSCs) as active contributors to pathologic events influencing neurogenesis. We utilized the Web of Science (core collection) as the data source.MethodsThe search was performed in the Web of Science core collection database until April 30, 2024, with the terms “Mesenchymal stem cells” as the title and “neurogenesis” as the topic.ResultsA total of 407 papers about mesenchymal stem cells in neurogenesis published from 2004 to 2024 were retrieved. Further, we performed a bibliometric analysis of these publications, such as generating cooperation maps, co-citation analysis of journals and references, and cluster analysis of keywords. Next, we discussed the mechanism by which MSCs promote neurogenesis during the onset of Alzheimer’s disease (AD) and stroke diseases.ConclusionOverall, three aspects primarily reflect the treatment of stroke with MSCs: neural circuit reconstruction, mitochondrial transfer, and extracellular vesicle transfer. The treatment of AD with MSCs is mainly reflected in the five aspects of inhibiting neuroinflammation, microglia changes, amyloid-β removal, functional recovery of autophagy, and blood–brain barrier (BBB) function recovery. Finally, we also made prospects for future research of MSCs.